The growth-employment-poverty nexus in Latin America in the 2000s: Peru Country Study - Cruces, Guillermo Antonio (2015)
The Peruvian economy performed exceptionally well between 2000 and 2012, with a growth performance that placed the country well above the regional average and an improvement in all labour market indicators. The economy suffered a slowdown as a consequence of the international crisis of 2008, but Peru sustained positive GDP growth rates during that episode and had only a small reduction in GDP per capita. The only labour market indicators impacted by the international crisis were the employment structure by educational level and the percentage of registered workers which suffered a slowdown in their improving trends.